Interface-resolved direct numerical simulations of sediment transport in a turbulent oscillatory boundary layer. (25th February 2020) - Mazzuoli, Marco; Blondeaux, Paolo; Vittori, Giovanna; Uhlmann, Markus; Simeonov, Julian; Calantoni, Joseph
Abstract : Abstract : The flow within an oscillatory boundary layer, which approximates the flow generated by propagating sea waves of small amplitude close to the bottom, is simulated numerically by integrating the Navier–Stokes and continuity equations. The bottom is made up of spherical particles, free to move, which mimic sediment grains. The approach allows one to fully resolve the flow around the particles and to evaluate the forces and torques that the fluid exerts on their surface. Then, the dynamics of sediments is explicitly computed by means of the Newton–Euler equations. For the smallest value of the flow Reynolds number presently simulated, the flow regime turns out to fall in the intermittently turbulent regime such that turbulence appears when the free-stream velocity is close to its largest value but the flow recovers a laminar-like behaviour during the remaining phases of the cycle. For the largest value of the Reynolds number, turbulence is significant during almost the whole flow cycle. The evaluation of the sediment transport rate allows one to estimate the reliability of the empirical predictors commonly used to estimate the amount of sediments transported by sea waves. For large values of the Shields parameter, the sediment flow rate during the accelerating phases does not differ from that observed during the decelerating phases. However, for relatively small values of the Shields parameter, the amount of moving particles depends not only on the bottom shear stress but also on flow acceleration. Moreover, the numerical results provide information on the role that turbulent eddies have on sediment dynamics.